Insulin sensitivity and blood glucose level of sepsis patients in the intensive care unit - Suhaimi F.M.; Jamaludin U.K.; Razak N.N.A.; Nor M.B.M.; Ralib A.M.; Shukeri W.F.W.M.; Hasan M.S.; Abu-Samah A.; Azman N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biomedical engineering; Blood; Diagnosis; Glucose; Insulin; Antibiotic resistance; Blood glucose level; Clinical experience; Clinical outcome; Critically-ill patients; Glycemic control; Insulin sensitivity; Sepsis; Intensive care units